Non-model systems in mammalian forelimb evo-devo. (August 2021) - Howenstine, Aidan O; Sadier, Alexa; Anthwal, Neal; Lau, Clive LF; Sears, Karen E
Abstract : Mammal forelimbs are highly diverse, ranging from the elongated wing of a bat to the stout limb of the mole. The mammal forelimb has been a long-standing system for the study of early developmental patterning, proportional variation, shape change, and the reduction of elements. However, most of this work has been performed in mice, which neglects the wide variation present across mammal forelimbs. This review emphasizes the critical role of non-model systems in limb evo-devo and highlights new emerging models and their potential. We discuss the role of gene networks in limb evolution, and touch on functional analyses that lay the groundwork for further developmental studies. Mammal limb evo-devo is a rich field, and here we aim to synthesize the findings of key recent works and the questions to which they lead.